Pemanfaatan limbah kulit udang sebagai bahan baku biopolimer dalam injeksi polimer - Ulfah, Baiq Maulinda; Fathaddin, Muh Taufiq; Ratnaningsih, Dyah Rini (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
The amount of shrimp shell waste is quite abundant in Indonesia, but its utilization is not optimal. Shrimp shells contain chitin that can be processed into chitosan. Chitosan polymer can be developed for Enhanced Oil Recovery. Testing the characteristics of shrimp shell chitosan has been carried out, but the recovery factor results in coreflooding are still very small. Additional characteristic tests such as adsorption tests are needed. This study was conducted to determine the characteristics of shrimp shell chitosan polymers by conducting tests such as compatibility tests, viscosity, adsorption. In this study, an experiment was conducted using biopolymer-chitosan with shrimp shell raw materials. The material for making formation water used NaCl with a salinity of 10,000 and 20,000 mg/L. The concentration of chitosan biopolymer was varied with 5,000, 10,000, and 15,000 mg/L. The size of the sand grains used was 60 mesh. The results of the tests that had been carried out all samples were declared compatible for use. The highest viscosity value was 1,055.19 cP and adsorption was 26.63 mg/g.